Holiday Effect of Ozone Pollution in China - Sijun Chen; Jun Chen; Jiangyong Li; Daocheng Gong; Boguang Wang (Atmosphere)
Over recent decades, China has achieved significant progress in reducing haze pollution, yet photochemical pollution, primarily characterized by elevated ozone (O3) levels, has intensified, posing severe ecological and public health risks. The “holiday effect”—periodic changes in human activities during holidays such as weekends and the Spring Festival—provides a critical lens to evaluate anthropogenic influences on O3 pollution, particularly under scenarios of reduced anthropogenic emissions driven by the carbon neutrality pledge. However, a comprehensive summary of this phenomenon remains lacking. This review systematically examines spatial–temporal variations and driving factors, including precursor emissions, atmospheric oxidation capacity (AOC), and meteorological conditions, of the holiday effects across China. Key findings reveal that reduced nitrogen monoxide during holidays weakens its titration effect on O3. Additionally, decreased particulate matter on holidays leads to improved atmospheric visibility and a corresponding enhancement in AOC and biogenic volatile organic compound emissions, all of which boost the photochemical formation capacity of O3. Furthermore, solar radiation and temperature positively correlate with O3 pollution during holidays, whereas rainfall and cloud cover suppress it. This review also provides suggestions for future research regarding mechanistic studies on photochemistry, machine learning for pollution drivers, radical roles in O3 formation, and health impact assessments.